Fenologia, caracterização físico-química de frutos e sementes de Bromelia balansae no Município de Santo Cristo - RS - Cariolatto, Letícia Paim (2019)
Bromeliads are species that adapt in different environments they can be used as ornamentation in the Northern region of Santa Catarina for medicinal purposes in the production of expectorant syrups and in the state of São Paulo its cultivation is restricted to the use of life fences. Knowing the development characteristics of they native fruit allows the maintenance and conservation of biodiversity and the resources available in nature. In this context, it was aimed to know the phenology of flowering and fruiting of a population of Bromelia balansae, and to know the physical and chemical aspects of its fruits and the germinative development of its seeds. The phenological study was performed daily, between the months of (January/2018 to May/2018), in relation to the vegetative development three inflorescences were submitted to evaluation. The parameters evaluated, phenology: (height and diameter; number of leaves and leaf diameters, beginning of the floral escapery, floral bud, open flowers, senescence, initial and final fruiting), physical: (average length of fruits, number of fruits, weight and Fruit color), chemical analyses: (total titratable acidity, soluble solids, hydrogenionic potential), seeds: (seed diameter, weight and germination in vegetative chamber and in tubes and vigor test). The phenological Study was developed in the city of Santo Cristo and the other tests at the Federal University of the Southern Frontier in the municipality of Cerro Largo. The results showed that there was no phenotypic difference in relation to the time of the phenophases, the production of fruits was low, compared to other studies with the same species, indicating that the environment can influence the expressive quantity of fruits of bromeliad . The fruits showed variations regarding physicochemical parameters, high pH levels and total soluble solids, indicating low yield and industrial interest of fruit pulp. In relation to seeds, the batches presented low humidity, the germination tests showed positive results for seed germination.